Assessment of Left Ventricular Dyssynchrony and Cardiac Function in Patients with Different Pacing Modes Using Real-Time Three-Dimensional Echocardiography: Comparison with Tissue Doppler Imaging - Waseem Ahmed (Al-Azhar University, Faculty of Medicine (Damietta), 2019)
Background: Previous studies revealed that right ventricle apex pacing with different modes may yield abnormal electrical activity and left ventricle dyssynchrony.Aim of the work: To evaluate systolic function of left ventricle and mechanical dyssynchrony with different modes of pacing using real time three dimensional echocardiography [the RT3DE] and tissue Doppler imaging [TDI].Patients and Methods: The study included thirty-five individuals with permanent dual chamber pacemaker with atrial leads placed in right atrial appendage and right ventricular leads placed in right ventricular apex, the pacemakers were programmed to different modes. Imaging parameters were obtained following pacing for 24 hours in each mode.Results: The results revealed that the RT3DE and TDI-derived dyssynchrony indices in the atrial demand pacing [AAI] mode were significantly lower than those in the dual chamber demand pacing [DDD] and ventricular demand pacing [VVI] modes; however, there was no significant difference between the DDD and VVI modes. Also, left ventricular ejection fraction [LVEF] during AAI and DDD modes was significantly higher than that during VVI mode; however, there was no significant difference between the DDD and AAI modes. There were negative correlations between LVEF and Ts-MD and Ts-SD, and there was positive strong correlation between RT3DE and TDI-derived dyssynchrony indices.Conclusions: Left ventricular systolic synchronicity in AAI mode was superior to that in DDD and VVI modes. Left ventricular ejection fraction in the AAI and DDD pacing modes are superior to that in the VVI mode.